2019
DOI: 10.1287/serv.2019.0247
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Base-of-the-Pyramid Concept

Abstract: The Base-of-the-Pyramid (BoP) concept plays a prominent role among the market-based perspectives for poverty alleviation. Previous literature reviews discuss the evolution of the BoP concept as a research domain, however several major research streams that approach the phenomenon from distinct angles have been overlooked. To address these shortcomings, we continue these reviews and formulate recommendations for theoretical and empirical advancement by considering emerging research domains. We use the problemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 115 publications
0
13
0
Order By: Relevance
“…It is observed a heterogeneous scientific production in time on the topic under analysis, which shows the emergency of continuing the research on the same, especially when sustainability is a common global goal in which sustainable and inclusive economic growth is postulated. This means that inclusive entrepreneurship is a conduit for such growth because, as argued by Joncourt et al (2019), from a management perspective, it is essential that managers understand the need to explore pyramid-based activities by assuming an entrepreneurial role to create and manage inclusive innovations, where inclusion of disadvantaged people can occur within and outside the workplace, with offering organizational access to important resources at the institutional level (Fujimoto and Uddin, 2020). The Sankey diagram (Figure 4) allows visualizing the main items on three distinct fields and how they relate to each other.…”
Section: Performance Analysis and Science Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed a heterogeneous scientific production in time on the topic under analysis, which shows the emergency of continuing the research on the same, especially when sustainability is a common global goal in which sustainable and inclusive economic growth is postulated. This means that inclusive entrepreneurship is a conduit for such growth because, as argued by Joncourt et al (2019), from a management perspective, it is essential that managers understand the need to explore pyramid-based activities by assuming an entrepreneurial role to create and manage inclusive innovations, where inclusion of disadvantaged people can occur within and outside the workplace, with offering organizational access to important resources at the institutional level (Fujimoto and Uddin, 2020). The Sankey diagram (Figure 4) allows visualizing the main items on three distinct fields and how they relate to each other.…”
Section: Performance Analysis and Science Mappingmentioning
confidence: 99%
“…On the other hand, when a search is carried out with a junction of similar terms on the topic under analysis, it is found that there is a minute amount of scientific documents in international online databases, a scarcity of systematic literature reviews (SLRs), which are crucial to map emerging themes in business research (Donthu et al, 2021), as is the topic studied here. Therefore, the research carried out resulted in a miscellany of scientific papers in a wide range of knowledge areas, in which the topics addressed range from the interaction between the sustainability pyramid and inclusion (Arora and Ali Kazmi, 2012;Joncourt et al, 2019;Labucay, 2015;Picciotti, 2017), the inclusive business approach (Lashitew et al, 2020;Skare and Golja, 2012;Susanto, 2019) and other inclusive actions, the importance of inclusive entrepreneurship and the creation of social value (Janeska-Iliev and Debarliev, 2020;Pilkov a et al, 2016;Zhao, Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A base (bottom) of the pyramid business model aims to simultaneously alleviate poverty and increase profitability by developing radical innovations to cater to the needs of poor and other vulnerable communities [13]. Bottom of the pyramid business models mainly operate in developing countries to convert the unaddressed needs of marginalised communities into profitable business opportunities, thus tapping into an unrealised market potential [19]. The value propositions generated by a bottom of the pyramid business model tend to be based on cost-effective solutions [13].…”
Section: Integrative Business Modelmentioning
confidence: 99%
“…The innovation process related to this type of business model is underpinned by the vision of co-creating solutions by iteratively engaging with communities and other stakeholders [20]. Some frequently cited examples include the Grameen Group, Hindustan Unilever Group, CEMEX, ITC Limited and the Bangladesh Rural Advancement Committee cf., [19,21,22].…”
Section: Integrative Business Modelmentioning
confidence: 99%
“…Conspicuous consumption traditionally has been observed as a behavior of the wealthy and upper class for showcasing their social status; however (Charles et al, 2009) observed that those in the lower classes are also engaged in conspicuous consumption. Researchers noted that people with low income have higher aspirations for conspicuous consumptions (Srivastava et al, 2020) and they are willing to sacrifice their basic needs for status consumptions (Joncourt et al, 2019), which also highlights the financial side. Therefore, a refined view has been added to the field of study as individuals of all classes are aspirants in gaining social status, which means consumers who care about social status are involved in conspicuous consumption.…”
Section: Introductionmentioning
confidence: 99%